2018
DOI: 10.1016/j.virol.2017.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Accessory proteins 8b and 8ab of severe acute respiratory syndrome coronavirus suppress the interferon signaling pathway by mediating ubiquitin-dependent rapid degradation of interferon regulatory factor 3

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV) is an inefficient inducer of interferon (IFN) response. It expresses various proteins that effectively circumvent IFN production at different levels via distinct mechanisms. Through the construction of recombinant IBV expressing proteins 8a, 8b and 8ab encoded by SARS-CoV ORF8, we demonstrate that expression of 8b and 8ab enables the corresponding recombinant viruses to partially overcome the inhibitory actions of IFN activation to achieve higher replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 72 publications
3
84
0
2
Order By: Relevance
“…These data indicate that orf8 genes underwent adaptations during transmission from animals to humans during the SARS epidemic. A limited functional analysis suggested that the ORF8a protein is dispensable for SARS-CoV replication in Vero E6 cells but may have a role in modulating endoplasmic reticulum 20,[65][66][67][68][69] . Whether and how these adaptations were involved in SARS-CoV virulence are not fully clarified.…”
Section: Variability Of Sars-cov In Humans and Civetsmentioning
confidence: 99%
“…These data indicate that orf8 genes underwent adaptations during transmission from animals to humans during the SARS epidemic. A limited functional analysis suggested that the ORF8a protein is dispensable for SARS-CoV replication in Vero E6 cells but may have a role in modulating endoplasmic reticulum 20,[65][66][67][68][69] . Whether and how these adaptations were involved in SARS-CoV virulence are not fully clarified.…”
Section: Variability Of Sars-cov In Humans and Civetsmentioning
confidence: 99%
“…However, whereas glycosylation at N81 stabilized protein 8ab and protected it from proteasomal degradation, protein 8b was highly unstable and underwent rapid proteasomal degradation [168]. The ubiquitinated 8b and 8ab may mediate rapid degradation of IRF3 and regulate host antiviral innate immunity [169].…”
Section: Ptms Of Coronavirus Accessory Proteinsmentioning
confidence: 99%
“…A study involving MERS-CoV described that ORF 8b strongly antagonizes the INF-beta (β) promoter and ORF4b and 8b significantly suppress IFN induction (Lee et al, 2019b). Accessory proteins 8b and 8ab of SARS-CoV can suppress the INF-β signaling pathway (and thus interferon production) by their participation in the ubiquitin-mediated rapid degradation of INF regulatory factor 3 (IRF3) (Wong et al, 2018). In contrast, when we focused on MERS-CoV from bats and camels, ORF 8b antagonized melanoma differentiation-associated protein 5-mediated nuclear factor kappa B (NF-κB) activation.…”
Section: Phylogenetic Profilingmentioning
confidence: 99%